UJI AKTIVITAS ANTIFUNGI DARI EKSTRAK ETANOL 96% BUNGA KECOMBRANG YANG MENGINFEKSI TANAMAN KOMODITAS HORTIKULTURA SPESIES TOMAT (Solanum tuberosum L) - Firman Rezaldi; Mu'jijah Mu'jijah; Heny Sasmita; Ucu Wandi Somantri; M. Fariz Fadillah; Muhammad Faizal Fathurrohim (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2021)
Tomatoes are one of the horticultural commodity crops that are easy to obtain and have various benefits such as being a functional food ingredient and an active ingredient in medicines and cosmetics. Tomatoes contain bioactive compounds, especially vitamin C, which plays an important role as a source of antioxidants, anti-inflammatory, antibacterial, antifungal and anticancer. The increasing productivity of tomato plants is one of the targets for every horticultural farmer to distribute to various industries, both food and pharmaceutical industries. Tomatoes, which are one of the horticultural commodity crops, are easily damaged, have a short shelf life, rot and also wilt easily, which can be caused by attacks by pathogenic fungi, namely Fusarium oxysporum and Fusarium solani. The solution to overcome these two attacks by pathogenic fungi is to use herbal plant extracts which are quite environmentally friendly and have pharmacological activity in inhibiting the growth of pathogenic fungi, one of which is the ethanol extract of kecombrang flowers. This research aims to provide the latest scientific information regarding the potential of 96% ethanol extract from kecombrang flower plants with concentrations of 1%, 3% and 5% in inhibiting the growth of both pathogenic fungi. Tests for the inhibition of the growth of these two pathogenic fungi were carried out using the well method. The results of this research have proven that kecombrang flower plant extract has overall inhibitory power and a concentration of 5% is the optimal treatment in inhibiting the growth of both pathogenic fungi.